Pengaruh Pilihan Jenis Sekolah Menengah Negeri dan Swasta Terhadap Masa Peralihan Sekolah-Bekerja di Indonesia - Ruth Eviana Hutabarat; Kartika Sari (Nomicpedia: Journal of Economics and Business Innovation, 2022)
This research aims to examine how the choice of public and private secondary schools (SMP-SMA) influences the decision to transition after graduating from high school. This study uses a quantitative approach, utilizing data from the fifth batch of the Indonesian Family Life Survey (IFLS) (2014) with 3209 observations from all over Indonesia using logistic multinomial regression analysis. The results of this study indicate that individuals who graduate from private schools have a positive value of 0.056 toward the tendency to work informally. Graduates of private and public high schools tend not to work formally by 7.2% and 10.9%, respectively. Male individuals will tend to work informally and formally, with a coefficient of 0.069 and a coefficient of 0.271, while female individuals tend to continue their higher education with a coefficient of (0.120). The variable of the highest level of education completed by the head of the household has a negative coefficient for both the formal and informal sectors, while college has a positive coefficient. This shows that the higher the level of education of the head of the household, the individual tends to continue studying at university, with a coefficient value of 0.083.